On the problems of the structure of the Special part of the Code of Civil Procedure of the Republic of Belarus - Skobelev, Vladimir P. (Journal of the Belarusian State University. Law, 2026)
The structure of the Special part of the Code of Civil Procedure of the Republic of Belarus is analysed and some of the problems associated with it are identified. In particular, it is shown that section VI of the Code of Civil Procedure of the Republic of Belarus is overloaded with normative material; general norms are not always properly distinguished from special norms; the rules on summary proceedings are unjustifiably divided into two independent groups; proceedings on cases arising from administrative and other public legal relations lack a number of structural elements devoted to individual categories of cases of this type of proceedings; norms related to the same type of proceedings are «scattered» throughout the text of the Code of Civil Procedure of the Republic of Belarus, etc. The author proposes a concept for the structure of the Special part of the Code of Civil Procedure of the Republic of Belarus that allows for the resolution of all the noted problems.
Keywords: civil procedure; structural elements of the code; general part; special part; section; subsection; chapter; paragraph